4/2000 organic law: history separation of a and reason your legal blur - Ruiz de Huidobro de Carlos, José M.ª (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
This article offers a very unfavourable initial assessment of the recent organic law 4/2000 of January the 11th on the rights of foreigners and their integration into society inSpain. Such an initial assessment is the result of the way that the legislative process has been carried out. On the one hand, a rupture of the basic consensus has explicitly occurred in its final phase; political parties had been maintaining this consensus on the way, broadly speaking, of how to face the foreign migration phenomenon, not only legislatively speaking, but also from the point of view of the specific policies to be implemented; with this breaking up of the consensus there is a risk: that immigration policy —a State matter— is included in the immediate electoral agenda of the political parties, whose present features do not favor either calm or rigor in the debate. On the other hand, the way in which the Organic Law 4/2000 has been drafted —a rereading of law 7/1985 with a look to immigrants’ integration into society— has not made easier its correct technical-legal approach; this is because, over the model of a simple and plain immigration law as the Organic Law 7/1985 was, it is almost impossible to draw up an immigration law which promotes immigrants’ integration into society with a minimum of legal quality and coherence.